Wings of ink eaudiobook - Steffort, Angelina J. (Wings of Ink, 2024)
The seductive and thrilling first book in the Wings of Ink epic romantic fantasy series from award-winning author Angelina J. Steffort. Stuck in prison, pirate Wolayna Milevishja is waiting to be dealt her punishment—one worse than death, her captors promised when they closed the door of her cell over nine months ago. Now that punishment has come to collect her. Wolayna is taken to the mystical fairylands as this year's bride for the Crow King, and that, even the humans in this world know, means there is no hope. As Wolayna quarrels with her fate, frosty disdain melts into heart-stopping attraction, and she realizes that, maybe, King Myron, has just as little choice as she has. Something ancient and vengeful is at work in the Crow realm, and the intrigue at court is just the surface of the looming danger closing in on them. Will Wolayna outsmart fate and find the freedom she's owed, or will this new world of winged horror and surprising beauty be the death of her? If you like witty, independent heroines and morally-grey, tormented heroes, you will devour this sizzling, addictive fantasy adventure. Perfect for fans of A Court of Thorns and Roses, From Blood and Ash, and Beauty and the Beast, WINGS OF INK is an epic romantic fantasy with enemies-to-lovers, arranged marriage, slow-burn spice, and a magical world filled with mysteries and monsters.